Myocardial involvement in Behcet's disease may be higher in patients with Neuro-Behcet's disease: a speckle tracking echocardiographic study - ÖZBEN SADIÇ, BESTE; ENGİN, ESİN; ALİBAZ ÖNER, FATMA; MİDİ, İPEK; SÜNBÜL, MURAT; SAYAR, NURTEN; DİRESKENELİ, RAFİ HANER; KUTLUĞ AĞAÇKIRAN, SEDA (TAYLOR & FRANCIS LTD, 2022)
Background Behcet's disease (BD) may present with life threating complications including neurological and cardiovascular involvement. Neuro-Behcet's disease (NBD) is one of the most important causes of morbidity and mortality in patients with BD. The aim of the present study is to investigate whether patients with NBD are different than BD patients with other manifestations in terms of subclinical myocardial dysfunction. Methods Forty patients with NBD (23 female, mean age: 42.4 +/- 9.4 years), 40 patients with BD (9 female, mean age: 39.7 +/- 9.0 years) and 40 controls (20 male, mean age: 41.8 +/- 6.5 years) were consecutively included in the study. All subjects underwent a transthoracic echocardiography for evaluation of left ventricular (LV) and atrial (LA) functions with two-dimensional (2D) speckle tracking echocardiography (STE). Results Baseline characteristics, clinical data, LV dimensions, systolic and diastolic functions were all in normal range among the groups. LV global longitudinal strain (LV-GLS) was significantly lower in patients with NBD and BD patients without neurologic involvement compared to controls. LA conduit strain was significantly lower in patients with NBD compared to controls. Patients with both parenchymal NBD and vascular NBD manifestations had significantly lower LV-GLS and LA conduit strain compared to controls. Linear regression analysis demonstrated that among cardiovascular risk factors only presence of NBD was the independent predictor of LV-GLS. Conclusions BD is associated with impaired LV and LA functions. LV-GLS and LA conduit strains of the patients with NBD were lower. NBD was an independent predictor of LV-GLS, suggesting a link between neurological manifestations and cardiac dysfunction in BD patients.
Keywords: Behcet's disease; Neuro-Behcet's disease; cardiac involvement; speckle tracking echocardiography; HEART-RATE-VARIABILITY; VENTRICULAR DYSSYNCHRONY; AUTONOMIC DYSFUNCTION; EUROPEAN ASSOCIATION; AMERICAN SOCIETY; UPDATE; RECOMMENDATIONS; MORBIDITY; MORTALITY; DIAGNOSIS